THE COMPLEMENTARY ROLE AND IMPACT OF WORKSHOPS ON STUDENTS IN FASHION DESIGN EDUCATION AT AMITY UNIVERSITY GWALIOR - Rastogi, Twinkle; Thakuriya, Kajal; Munjal, Kalpana (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the realm of higher education, where academic pursuits intersect with market dynamics, the intrinsic value of fundamental design principles becomes pronounced. This is particularly pertinent in disciplines like fashion design, where students are immersed in a distinctive and specialized learning environment to bolster their efficacy and proficiency. Amidst this backdrop, workshops have emerged as a pivotal cornerstone within fashion design education, recognized universally as an imperative priority. Modern education calls for innovative approaches, and workshops epitomize this evolution. Their significance extends beyond traditional pedagogical methods, offering students a platform to not only comprehend theoretical concepts but also apply them in practical, industry-relevant contexts. These workshops foster a dynamic learning atmosphere, aligning education with the ever-evolving demands of the market. One of their key advantages lies in facilitating direct interaction between students and industry experts, bridging the chasm between academia and real-world design scenarios. This study delves into the essence of workshops as a complementary facet of fashion design studies, with a specific focus on those conducted at the renowned Amity School of Fashion Design and Technology in Gwalior. At its core, the study seeks to unravel the multifaceted aspects surrounding workshops, exploring their necessity, importance, and transformative impact. To embark on this exploration, the research methodology employs a comprehensive and multifarious approach. It encompasses quantitative data collection techniques, through likert scale meticulously analyzing the objective, outcomes, and feedback derived from design students who actively participated in these workshops. The results of this study illuminate a significant gap in traditional fashion design education—a gap that workshops seamlessly fill. These dynamic learning experiences empower students with practical skills and insights that transcend conventional classroom instruction. The findings underscore the symbiotic relationship between workshops and holistic learning, as students' personal and professional growth experiences an unprecedented upswing. Furthermore, the study captures the resounding endorsement from students themselves, as their feedback substantiates the pivotal role of workshops in enhancing their educational journey. In essence, this study bridges the theoretical-practical divide that often hampers comprehensive education. It spotlights the transformative potential of workshops, redefining their status from peripheral add-ons to integral components of the educational framework. By spotlighting the case of Amity School of Fashion Design and Technology in Gwalior, the study provides a template for educational institutions worldwide to infuse innovation, relevance, and efficacy into their curriculum through the strategic integration of workshops.